Bacillus sp. 123, una cepa aislada de suelos agrícolas con potencial para degradar diferentes antibióticos - Sauka, Diego Hernan; Areco, Vanessa; Peralta, Cecilia; Marozzi, Antonela Alejandra; Del Valle, Eleodoro Eduardo; Palma, Leopoldo (Asociación Argentina de Microbiología, 2023)
Poster y resumen